Rancang Bangun Sistem Informasi Kelurahan Menggunakan Metode Prototype di Kelurahan Rantau Indah - Nugroho Ardy Pramono; Jefri Marzal; Ulfa Khaira (Jurnal Informatika Universitas Pamulang, 2022)
In modern times like today, almost every field of human work demands that everything be done quickly and effectively, including in terms of service to the government process, but currently the Rantau Indah village in providing services to the community still uses conventional methods of making outgoing letters such as certificates. unable, birth certificates, and others have to come and then wait at the kelurahan office for quite a long time to complete the letters, so many people complain about this. In helping to realize a better service, an information system is needed. The design and manufacture of this kelurahan information system has the main focus as a mail service medium that aims to facilitate the service process at the Rantau Indah subdistrict office as well as a wider kelurahan access facility for the community itself. A web-based urban village information system that can be accessed through certain pages using PC and smartphone devices, was built using the prototype method where the process flow consists of data collection, rapid design, making prototypes in the form of UML and mock-ups then implementation into a programming language (coding) and the last is final system testing and improvement accompanied by periodic system maintenance. The testing process uses the black-box method where the system is tested to get a conclusion whether there are still errors or not by paying attention to the black-box testing steps based on previous research references. From this test, a conclusion is made of the success and failure of the system which will later become a benchmark for the success of the system being built. Functional errors or errors that are still in the system are then repaired and refined until the system can work properly when used.